Kontribusi Supervisi Klinis dalam Meningkatkan Kualitas Pengajaran: Studi Kasus di MIS Trubus Iman - Ramadhina, Marini Shadrina; Sudadi, Sudadi (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to explore the implementation of clinical supervision in Islamic schools, with a particular focus on its contribution to improving teaching quality. Additionally, the study seeks to identify the factors influencing the success of clinical supervision within this context.Method – This research employs a qualitative descriptive approach. Data were collected through structured interviews with school principals and teachers at MIS Trubus Iman, as well as field observations. Data analysis followed the stages of qualitative analysis, including data collection, data reduction, data presentation, and conclusion drawing. Findings – The research findings indicate that face-to-face clinical supervision between school principals and teachers significantly enhances teachers' reflection on their teaching practices and provides constructive feedback. The structured supervision process, including preparation, observation, and feedback sessions, enables teachers to better understand the strengths and weaknesses of their teaching methods. However, the study also identifies challenges such as time constraints and limited management support, which hinder the full effectiveness of the supervision process. Research Implications – This study emphasizes the need for continuous professional development through clinical supervision to enhance the quality of teachers' instruction. However, the research is limited to a single school's context, necessitating further studies in other Islamic schools to validate the findings and broaden the understanding of clinical supervision within this context.